PERBANDINGAN KADAR TIROKSIN (T4) dalam CAIRAN FOLIKEL OVARIUM UKURAN KECIL, SEDANG dan BESAR SAPI POTONG - , SITI RAKHMA AFRIANA; , Dr. drh. Rr. Amelia Hana, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hormone thyroxin is one of the best indicators of the reproduction. Thyroid hormone plays a role in growth, metabolism, and reproduction. One of the hormones produced by the thyroid is the hormone thyroxin (T4). This study aims to determine the levels of T4 in the ovarian liquor folliculi of bovine small follicles (<5 mm), medium follicles (5-10 mm), and large follicles (> 10 mm). This study uses 15 follicles obtained from RPH Giwangan. Follicles are distinguished by size into small follicles (<5 mm in diameter, n = 5), medium follicles (5 to 10 mm in diameter, n = 5), and large follicles (> 10 mm in diameter, n = 5). Each ovary was isolated by the method of aspiration to obtain follicular fluid, and analyzed by ELISA (Enzyme Linked Immunoassay). The result of measurements of the average T4 level was 15.04 + 2.01 ng/dL for small follicles, 13.69 + 3.44 ng/dL for medium follicles, and 14.69 + 2.20 ng/dL for large follicles. There is no significant difference (P > 0.05) between the average levels of the hormone T4 in each bovine liquor folliculi. The conclusion of this study is T4 levels in small follicles, medium follicles and large follicles are similar.